Plan de gestión para la puesta en marcha y adaptación a funcionamiento normal de la nueva sede del área de Salud Mora Palmichal - Monge-Fonseca, Fabio (Instituto Tecnológico de Costa Rica, 2015)
This document treats about the proposal of a management plan for commissioning and adapting at normal operation the new headquarter Mora-Palmichal (ASMP, in Spanish "Area de Salud Mora Palmichal") of the Caja Costarricense de Seguro Social. The main purpose is to prepare the branch to improve effectively the quantity and quality of the services provides to the local population, in compliance of the current healthcare model of the country. To achieve this purpose, a mixed research method (descriptive and explanatory) was developed, because, with the use of the project administration and change management theories, was proposed an improvement solution in the project planning process, specifically in the commissioning of new infrastructure within the organization. Therefore, improvement opportunities were identified through the lessons learned and internal processes of the company, which are factors that could influence the project development, while, the change management factors were integrated by applying project management knowledge. The application of the project management good practices and the research results, delivers a management plan proposal that will allow the ASMP execute an appropriate and controlled change management process, in order to satisfy the needs to generate the regular operations mood of the new branch. Keywords Improvement opportunities, lessons learned, environmental factors, management change, project management, new infrastructure.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos. 2015.
Keywords: Salud; Riesgos ambientales; Gestión de proyectos; Infraestructura; Factores